2014
DOI: 10.1186/1471-2334-14-356
|View full text |Cite
|
Sign up to set email alerts
|

The impact of central line insertion bundle on central line-associated bloodstream infection

Abstract: BackgroundKnowledge about the impact of each central line insertion bundle on central line-associated bloodstream infection (CLABSI) is limited.MethodsA quality-improvement intervention, including education, central venous catheter (CVC) insertion bundle, process and outcome surveillance, have been introduced since March 2013. Outcome surveillances, including CLABSI per 1,000 catheter-days, CLABSI per 1,000 inpatient-days, and catheter utilization rates (days of catheter use divided by total inpatient-days), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 23 publications
3
35
0
2
Order By: Relevance
“…These findings are in concordance with other similar studies, where total resistance to amikacin and gentamicin was observed resistance among P. aeruginosa isolates in ICUs from other centres by Kaur, et al [5,18]. In the study by Tang, et al [6] Candida species compromised 4 CLABSI cases, and each one was caused by methicillin-resistant Staphylococcus aureus and coagulasenegative Staphylococci. Parameswaran, et al, in their study found MRSA to be responsible for 26.7% CRBSIs and single isolate of A. Baumannii resistant to all the routine drugs [8].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are in concordance with other similar studies, where total resistance to amikacin and gentamicin was observed resistance among P. aeruginosa isolates in ICUs from other centres by Kaur, et al [5,18]. In the study by Tang, et al [6] Candida species compromised 4 CLABSI cases, and each one was caused by methicillin-resistant Staphylococcus aureus and coagulasenegative Staphylococci. Parameswaran, et al, in their study found MRSA to be responsible for 26.7% CRBSIs and single isolate of A. Baumannii resistant to all the routine drugs [8].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, microbial biofilms may pose a public health problem for persons requiring indwelling medical devices [11]. Prevention development of records and multidisciplinary guidelines of care for central venous catheter insertion and maintenance (bundle care), cutaneous antisepsis, maximum sterile barrier, correct use of central venous catheter insertion technique; use of chlorhexidine-impregnated dressings; early catheter removal, use of antimicrobial catheters, and antimicrobial catheter lock solution [6,12]. Relatively few studies from south India have been conducted on central venous catheter associated bloodstream infections.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of maximal barrier precautions in reducing CLABSI has been demonstrated in various studies, both alone and as part of a multimodal approach [42,44,45]. This was recently reaffirmed by Tang et al, who studied the adherence to the components of the central line bundle and concluded that the use of maximal sterile barriers precautions during insertion was associated with a significantly lower CLABSI rate (OR, 0.14 [95 % CI, 0.03-0.71]) [46]. 4.…”
Section: Use Of Full Barrier Precautionsmentioning
confidence: 74%
“…One study implemented a central line checklist for the IHI care bundle items and discovered a low compliance with the item 'maximal sterile barrier precautions'. Not surprisingly, the analysis revealed that CLABSI was more likely to develop in patients in whom maximal sterile barrier precautions were not utilized and when central lines were inserted by non-intensivists [31]. Such results provide an indication of areas for improvement through stepwise introduction of new interventions.…”
Section: Applying Quality Improvement Strategiesmentioning
confidence: 70%